Integrating Extended Reality into Educational Contexts: Insights from a Postgraduate VR Course at UNIOESTE - Maurício, Claudio Roberto M.; Peres, Fabiana; Teixeira, João Marcelo; Santos, Wallesa D. M. Q. dos; Peretti, Adriano; Brecher, Andréia Aparecida; Santos, Lucas Rodrigues M. dos; Lee, Alan de Oliveira; Butzen, Lucia Renata da Silva (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
This paper presents the outcomes of a postgraduate course on virtual reality conducted at UNIOESTE in 2024, which aimed at bridging theoretical concepts and practical implementations of extended reality for educational purposes. Three student groups developed and piloted XR solutions: one focusing on immersive Geography lessons for Elementary School, another on virtual explorations of dinosaurs, and the third on augmented and virtual tools for teaching Mathematics. We discuss their experiences, reflect on the primary challenges encountered, and highlight future directions for XR technologies in diverse instructional contexts. The analyses are related to methodologies for integrating XR, user perspectives, barriers, innovation, and long-term sustainability.